Accumulation and wash-off characteristics of surface pollutant and identification of risk areas on urban land uses in a lakeside city, Wuxi, China. Issue 5 (28th May 2019) - Guo, Jiaxun; Pan, Ye; Zuo, Ping; Xu, Yunyun; Wang, Qingqing; Ma, Jinsong; Wang, Lachun
ABSTRACT: This paper selected administration and public services, residential areas, roads, green space, parking areas, industrial areas and commercial and business facilities in Wuxi city, China, to analyze the characteristics of pollution accumulation, wash-off and potential risk areas of pollutants over different urban land uses and pavement surface materials. Results showed that green space, residential areas and roads sequestrated higher pollutants than that of other land uses. Materials of masonry and cement pavement accumulated higher pollutant concentration than that on the marble and asphalt pavement. The potential risk areas of non-point source pollution were located in the old residential areas in the downtown region. The results of wash-off simulation showed that the first flushing effect was obvious during the initial period of rainfall. Eighty percent of the accumulative total nitrogen or total suspended solid could be washed-off during the first 25.6–50.2% period of the rainfall events.